Análise da estabilidade de edifícios altos com lajes lisas, nervuradas e nervuradas com vigas-faixa levando em consideração a interação solo-estrutura - Passos, Vinicius de Melo (2016)
Reinforced concrete buildings in the past were built with robust elements, providing great rigidity to structure regarding the stability of the same. With technological advances in construction over the years, arose construction systems that provided taller and slender buildings. Given that the global stability of tall and slender buildings is critical, we sought in this dissertation study some of the factors that influences the global stability of buildings of reinforced concrete, such as the type of construction system slab (flat slab, waffle slab and waffle slab with band beams), thickness of the slabs, the thickness of the hard core, coefficients that simulate the physical non-linearity of structural elements, floor height and the effect of soil-structure interaction. It was found that the above factors have influence on the global stability of buildings of reinforced concrete. Among these factors, we highlighted the coefficients that simulate the physical non-linearity of the structural elements and soil structure interaction, so that had a greater influence on global stability. For modeling and analysis of the results will be used the commercial software CAD / TQS version 17.13.